Interview with Raniyah Copeland, President and CEO of the Black AIDS Institute Discussing Black Feminist Leadership, and Black Women at Risk. Issue 2 (3rd July 2019) - Lyle Wilson, Anndretta
Abstract : As the new President and CEO of the Black AIDS Institute, Raniyah Copeland offers insight on her commitment to the organization being a model for nonprofit community based advocacy and intervention. Copeland shares ideas about collaborative Black solutions for Black people, and including Hollywood influencers in the effort to reach Black families. The Black AIDS Institute is the only national Black organization dedicated to ending HIV and supporting those living with HIV.